2013
DOI: 10.7314/apjcp.2013.14.5.2839
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MicroRNA-106 on Proliferation of Gastric Cancer Cell through Regulating p21 and E2F5

Abstract: Objective: To investigate the effects of miR-106b on malignant characteristics of gastric cancer cells, and explore possible mechanisms. Methods: Expression of miR-106b, p21 and E2F was determined by real-time PCR. Transfection with miR-106b mimics was conducted, and gastric cancer cells with miR-106b overexpression were obtained. Cells transfected with mimic mutants and those without transfection served as negative and blank controls, respectively. Flow cytometry and transwell assays were adopted to detect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 20 publications
(18 reference statements)
0
17
0
Order By: Relevance
“…Zhao et al found that E2F5 functioned as an oncogene with copy number gain in prostate cancer [32] and we also found the carcinogenesis of E2F5 in OC in this study. Moreover, upregulation of E2F5 has been observed in gastric cancer [33] and colorectal cancer [34]. And the upregulation of E2F5 was also identi ed in OC.…”
Section: Discussionmentioning
confidence: 94%
“…Zhao et al found that E2F5 functioned as an oncogene with copy number gain in prostate cancer [32] and we also found the carcinogenesis of E2F5 in OC in this study. Moreover, upregulation of E2F5 has been observed in gastric cancer [33] and colorectal cancer [34]. And the upregulation of E2F5 was also identi ed in OC.…”
Section: Discussionmentioning
confidence: 94%
“…13 Yao et al, have indicated overexpression of miR-106b shortened the G0/G1 phase and accelerated cell migration and invasion of gastric cancer cells. 14 Liu et al, demonstrated that miR-106b negatively regulated osteogenic differentiation of mesenchymal stem cells in vitro. 15 However, the role of miR-106b in the progression and development of RCC is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al found that E2F5 functioned as an oncogene with copy number gain in prostate cancer [32] and we also found the carcinogenesis of E2F5 in OC in this study. Moreover, E2F5 was reported to be upregulated in human cancers, such as gastric cancer [33] and colorectal cancer [34]. And the upregulation of E2F5 was also identified in OC.…”
Section: Discussionmentioning
confidence: 97%